Review Analisis Hubungan Penyakit Jantung Koroner Terhadap Risiko Stres - Syfa Dwi Andini (Publikasi Indonesia, 2022)
Coronary heart disease is a global health problem worldwide as it is the leading cause of death in cardiovascular disease. Cardiovascular disease is a condition where the heart and blood vessels do not function normally due to disorders, resulting in congenital heart disease, rheumatic heart disease, stroke and high blood pressure. According to the World Health Organization, the global prevalence of coronary heart disease increased to 23.3 million in 2010. Meanwhile, based on data from the American Heart Association (AHA) in 2010, it was the cause of 1 in every 6 deaths from coronary heart disease in the United States. Knowing the risk factors for a disease is very important in understanding early detection. Stress is one of the risk factors for coronary heart disease and is still widely considered trivial and gets less attention as early detection of the disease. This research is a literature study that will describe the relationship between stress risk factors and coronary heart disease. The purpose of this journal review is to determine the risk of stress disease. Literature findings from previous studies suggest that stress is associated with or affects the risk of coronary heart disease.